Sustainable tour operator practices: A case study of PT Destination Asia - Sinaga, Endang Komesty; Silalahi, Nova Novita; Eppang, Buntu Marannu (International Journal of Applied Sciences in Tourism and Events, 2025)
This study aims to analyze the implementation of sustainable tour operator principles based on Travelife criteria in enhancing the competitive advantage of PT Destination Asia, a tour operator company based in Bali. Although existing literature highlights the benefits of sustainability practices, there remains a research gap in understanding their practical application and impact at the tour operator level in Indonesia. This research adopts a descriptive qualitative approach using a case study method, with data collected through in-depth interviews and documentation. Key informants, including managers and relevant staff, were selected through purposive sampling. The findings reveal that PT Destination Asia has successfully integrated the four main dimensions of sustainability—management, socio-cultural, economic, and environmental—into its operations. The company demonstrates a strong commitment to transparency through its annual reports, offers authentic tourism products that promote local culture, establishes partnerships with local communities and sustainable business partners, and applies environmentally friendly transportation and accommodation practices. Theoretically, this study strengthens the existing literature on the importance of applying sustainability principles to build competitive advantage in the tourism industry. Practically, it provides a valuable reference for other tour operators and policymakers to encourage the adoption of sustainability in the travel sector. Furthermore, this research opens up opportunities for future studies to explore consumer perspectives in evaluating the effectiveness of sustainability implementation.